New method for assessing the susceptibility of glacial lakes to outburst floods in the Cordillera Blanca, Peru - Vilímek, Vit (2014)
Original abstract: This paper presents a new and easily repeatable method for assessing the susceptibility of glacial lakes to outburst floods (GLOFs) within the Peruvian region of the Cordillera Blanca. The presented method was designed to: (a) be repeatable (from the point of view of the demands on input data), (b) be reproducible (to provide an instructive guide for different assessors), (c) provide multiple results for different GLOF scenarios and (d) be regionally focused on the lakes of the Cordillera Blanca. Based on the input data gained from remotely sensed images and digital terrain models/topographical maps, the susceptibility of glacial lakes to outburst floods is assessed using a combination of decision trees for clarity and numerical calculation for repeatability and reproducibility. A total of seventeen assessed characteristics are used, of which seven have not been used in this context before. Also, several ratios and calculations are defined for the first time. We assume that it is not relevant to represent the overall susceptibility of a particular lake to outburst floods by one result (number), thus it is described in the presented method by five separate results (representing five different GLOF scenarios). These are potentials for (a) dam overtopping resulting from a fast slope movement into the lake, (b) dam overtopping following the flood wave originating in a lake situated upstream, (c) dam failure resulting from a fast slope movement into the lake, (d) dam failure following the flood wave originating in a lake situated upstream and (e) dam failure following a strong earthquake. All of these potentials include two or three components and theoretically range from 0 to 1. The presented method was verified on the basis of assessing the pre-flood conditions of seven lakes which have produced ten glacial lake outburst floods in the past and ten lakes which have not. A comparison of these results showed that the presented method successfully identified lakes susceptible to outburst floods (pre-flood conditions of lakes which have already produced GLOFs).